Women As Leaders: Improving Organizational Performance Through Communication, Commitment, and Organizational Culture In The Kupang City Investment and Integrated Service Office - Stefanie N.B Burin; David Manafe (Jurnal Inada: Kajian Perempuan Indonesia di Daerah Tertinggal, Terdepan, dan Terluar, 2022)
The current leadership is not only occupied by men, but women have also dominated. There is a patriarchal culture in society which gives rise to the view that women are incapable of leading an organization. Even though women also have the same potential. The results of this study are expected to show that patriarchal culture does not apply in terms of leadership in this institution. Agencies in this case the Kupang City Investment and Integrated Services Office need to know the impact of women's leadership, communication of women leaders, organizational culture on the performance of employees as evaluation material in strategizing and improving performance results both from the amount of investment value and Community Satisfaction Index value. This study used quantitative methods, with a sample taken from the entire population of 54 employees at the Kupang City Investment and Integrated Services Office. Data collection uses questionnaires shared through Google Forms. This study used SEM-PLS as an analytical tool. The results showed that work power affects employee performance, women's leadership affects organizational culture, women's leadership affects employee performance, women's leadership affects organizational commitment, women's leadership affects communication, organizational governance affects employee performance, and women’s communication has no effect on employee performance. The results of the mediation test show that organizational culture mediates the influence of women's leadership on employee performance, organizational commitment mediates the influence of women's leadership on employee performance, and women's communication does not mediate the influence of women's leadership on employee performance.